2019
DOI: 10.1038/s41467-019-09309-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting bivalency de-represses Indian Hedgehog and inhibits self-renewal of colorectal cancer-initiating cells

Abstract: In embryonic stem cells, promoters of key lineage-specific differentiation genes are found in a bivalent state, having both activating H3K4me3 and repressive H3K27me3 histone marks, making them poised for transcription upon loss of H3K27me3. Whether cancer-initiating cells (C-ICs) have similar epigenetic mechanisms that prevent lineage commitment is unknown. Here we show that colorectal C-ICs (CC-ICs) are maintained in a stem-like state through a bivalent epigenetic mechanism. Disruption of the bivalent state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 63 publications
5
45
0
Order By: Relevance
“…As the catalytic subunit of PRC2, EZH2 plays an essential role in tumor progression. Previous study has revealed that targeting EZH2 inhibits CSC self-renewal and enhances the sensitivity of CRC to OXA [13][14]. In the present study, we found that knockdown of TRIM25 decreased the protein level of EZH2 (Fig.…”
Section: Trim25 Regulates Ezh2 Stability In Crc Cellssupporting
confidence: 67%
See 3 more Smart Citations
“…As the catalytic subunit of PRC2, EZH2 plays an essential role in tumor progression. Previous study has revealed that targeting EZH2 inhibits CSC self-renewal and enhances the sensitivity of CRC to OXA [13][14]. In the present study, we found that knockdown of TRIM25 decreased the protein level of EZH2 (Fig.…”
Section: Trim25 Regulates Ezh2 Stability In Crc Cellssupporting
confidence: 67%
“…Previous studies have identi ed the driving role of EZH2 in stem cell self-renewal. In CRC, EZH2 functions as a transcriptional repressor to downregulate IHH, a key gene responsible for normal colonocyte differentiation, resulting in improvement of self-renewal capacity of CSC [14]; in breast cancer, EZH2 increases NOTCH1 expression by directly binding to the NOTCH1 promoter and further promotes CSC properties or expands CSCs [16]. Besides its canonical function via regulation of H3K27me3, EZH2 is reported to increase the self-renewal capacity of CSC through binding to some non-histone targets, such as STAT3, NF-kB and β-catenin [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NHEJ1 is a core component of the non-homologous end joining (NHEJ) pathway that conducts DNA double strand break repair and maintains genome stability [39, 40]. Indian hedgehog (IHH) signaling regulates differentiation of colonocytes while epigenetic activation of IHH causes decreased self-renewal of colorectal cancer-initiating cells and increased sensitivity to chemotherapy [41][42]. We speculate that the prognostic lncRNA AC097468.7 is involved in the regulation of these pathways through interactions with adjacent protein-coding genes.…”
Section: Resultsmentioning
confidence: 99%